Experimental study on characteristics of flame propagation and pressure development evolution during methane-air explosion in different pipeline structures - Si, Rongjun; Zhang, Leilin; Niu, Yihui; Wang, Lei; Huang, Zichao; Jia, Quansheng; Li, Ziran (Frontiers in Earth Science, 2024)
A gas explosion experimental system based on a piece of 15 m-long and φ180 semi-closed wide open steel pipe was constructed. An explosion experimental study on straight pipelines and pipeline structures with different angles (45°, 90°, and 135°) was conducted.Research results demonstrated that before the turn, flame propagation speed and flame sustaining time in different pipeline structures were consistent. With the increase of the distance away from the ignition source, the flame propagation velocity increases and the flame sustaining time decreases; at the turning point, the flame velocity suddenly decreases and the flame duration increases obviously. Meanwhile, the peak value of overpressure on the lateral wall of the turning corner is greater than that on the inner wall. Among the three different angles, the peak value of overpressure on the lateral wall of 135° bend is the highest. Different pipeline structures have great influence on gas explosion overpressure and flame propagation speed. These research conclusions provide theoretical references for gas explosion resistance in coal mines.